Spectroscopic and docking studies on the interaction between caseins and β-carotene. (30th July 2018) - Allahdad, Zahra; Varidi, Mehdi; Zadmard, Reza; Saboury, Ali Akbar
Highlights: Binding is impacted by protein conformation varying with environmental conditions. β-Carotene has the highest binding affinity to κ-casein among casein fractions. Van der Waals interactions are the main forces involved in the interaction. Caseins conformation dramatically changed in association with β-carotene. Abstract: Natural occurrence of β-carotene in bovine milk and the leading role of milk proteins in low-fat or fat-free dairy products necessitate investigating the possibility of interaction between β-carotene and casein constituting up to 80% of bovine milk proteins. In this study, molecular interaction of caseins and β-carotene was analyzed using fluorescence, UV–Vis absorption, circular dichroism (CD), and computer-aided molecular modeling. Casein and its fractions were bound to β-carotene with a binding constant of the order 10 4 M −1 and a 1:1 binding stoichiometry. The binding was favored at alkaline pHs, low ionic strength and temperatures. κ-Casein had the highest binding affinity to β-carotene, among casein fractions. The negative values of entropy and enthalpy changes and docking studies proved Van der Waals interactions are predominant forces in the binding process. The casein conformation was also altered through inducing a more folded structure in β-casein and a looser conformation in α- and κ-casein.